(untitled) (Journal of Naval Architecture and Marine Engineering, 2011)
This paper deals with the study of nonlinear MHD flow, with heat and mass transfer characteristics of an incompressible, viscous, electrically conducting and Boussinesq fluid on a vertical stretching surface with thermal stratification and chemical reaction by taking in to account the viscous dissipation effects. Adopting the similarity transformation, governing nonlinear partial differential equations of the problem are transformed to nonlinear ordinary differential equations. The Quasi-linearization technique is used for the non-linear momentum equation and then the numerical solution of the problem is derived using implicit finite difference technique, for different values of the dimensionless parameters. The numerical values obtained for velocity profiles, temperature profiles and concentration profiles are represent graphically in figures. The results obtained show that the flow field is influenced appreciably by the presence of viscous dissipation, thermal stratification, chemical reaction and magnetic field. DOI: 10.3329/jname.v7i1.3254